Romersk tasteinstrumentmusik i det 17. århundrede : Studier i Vatikanbibliotekets samlinger - Johnsson, Bengt; Bergsagel, John (Danish Yearbook of Musicology, 1980)
The keyboard music preserved in the Vatican Library in the collections Fondo Chigiano Q IV 24-29 and Q VIII 205-206, Fondo Barberino latino 4288 and Vaticana Musica 569 (abbreviated Vat . Mus. 569) comprises 273 pieces of varying lengths; toccatas, ricercari and liturgical versets as well as correntos, passacaglias and variations, which have not heretofore been the subject of attention, with the exception of a brief discussion of the Chigi collection in W. Apel's Geschichte der Orgel- und Klaviermusik bis 1700 (Kassel 1967) and a catalogue of the same collection by H.B . Lincoln published in the periodical L'Organo (Rome 1968). No one, however, has singled out Vat. Mus. 569, which is of interest for making a distinction between organ and harpsichord pieces. Furthermore, in this collection one encounters the names of such composers as Fabrizio Fontana (otherwise known only for the 12 ricercari published in Rome in 1677) and Giov. Batt. Ferrini, who is represented by 14 pieces, mostly dance movements. In the Chigi volumes occur pieces by Ercole Pasquini and Frescobaldi FolIowing a catalogue of the contents of the volumes specified, which includes a revision of both the rather hap-hazard Vatican Library catalogue and of Lincoln's listing of the Chigi pieces in the above mentioned article, the pieces are sorted in Chap. II according to instrument, organ or harpsichord. Chap. III contains a stylistic survey with reference to the works of Frescobaldi and the printed ricercari of Fontana. The investigation touches on melodic tonality, in respect to which the dance movements especiaIly show the fluctuation between modality and major/minor tonality so characteristic of the early Italian baroque. Attention is also called here to a number of melodic figures which point ahead to the coming Italian keyboard style. The mixture of old and new as regards tonality is also apparent with respect to harmony. The texture (Iike the titles) may be looked upon as suitable for the Qrgan or for the harpsichord: organ pieces are distinguished (except for the toccatas) by a simple, vocal melodic style and a predominantly contrapuntal texture, whereas pieces for harpsichord, as is apparent in the numerous dance movements, display a purely harmonic conception in the great difference of treatment accorded the right and left hands – the right usually playing a single-line melody, the left playing chords, often arranged in primitive groups. This may represent a transfer of music for a solo voice (vocal or instrumental) with lute accompaniment to the harpsichord, that is to say, a transcription. Compared with the dance movements by Frescobaldi, in which the voiceleading in the accompanying parts is more independent and frequently makes use of imitation, the dances in the Chigi and Vat. Mus. manuscripts are simpler. In the variation-pieces, such as Battaglia, Romanesca, Ruggiero, etc., such »pianistic« elements as double-stop passages, repeated-note figures , chains of trilIs, and such like occur. Among the forms used one finds such types as variation-ricercare and variation-canzona with rhythmically varied themes. The corrento movements show two styles: some are of the simple Italian type in triple rhythm with a »siciliano«-like dotting of the melody, others are of the more modern 6/4 type anticipating the French courante with its hemiola rhythm. In Vat . Mus . 569 there are two pieces labelled courante, one of which is »courante Avignone« with a double. This courante is found also in the so-called »Copenhagen Tablature« (see note 83), and the same applies to the sarabande in the same manuscript. The harpsichord pieces called »tastata« in Vat. Mus. 569 can perhaps be ascribed to Bernardo Pasquini, since alongside the title is written »Di Signor Bernardo«. Pasquini used the designation »tastata« in several of his harpsichord suites and these movements show the same arpeggio-figures as do the two in Vat. Mus. 569. Chap. IV discusses the hitherto unpublished Frescobaldi compositions from Chigi Q IV 27 and Q VIII 205. These include two toccatas, a corrento, a set of Ruggiero variations and three (perhaps four) hymn versets. The four first-mentioned pieces bear the ascription »Di Sign. G. Frescobaldi«, the hymn versicles (three of them) have simply »G.F.B.«. Frescobaldi sometimes signed himself »G. Fresco Baldi«, so the three initials could indicate that we here have variants of the already known versets of the same hymns inasmuch as both style and technique are related (ef. P. Pidoux's edition of Frescobaldi's keyboard music published by Bärenreiter, vol. IV). The 273 pieces from the collections in the Vatican Library comprise a significant contribution to the study of Italian keyboard music, especially with regard to composers in Rome around Frescobaldi and his successor F. Fontana. Vat. Mus. 569, which will soon be published (Edition Egtved) in an edition with commentary, was in all probability copied by a Roman organist, since the year of copying is given as 1663 followed by the annotation »Virginius Mutius sonabat, Anno Dm. 1661«. The present article shows that in the middle of the 17th century, when all the collections considered here were copied, a distinction can be observed between organ and harpsichord styles. In Vat. Mus. 569, furthermore, the designation »per Organo« and »per Cembalo« is actually specified in some cases. The numerous melodic figures which occur in the pieces distinctively for harpsichord continue the development of the English virginalists and Sweelinck (whose style Frescobaldi encountered during a stay in Flanders in 1607) and anticipate the Italian keyboard style of the end of the 17th and early 18th century represented by such names as Bemardo Pasquini and later Domenico Scarlatti.